Sealing materials effectiveness evaluation in the repair of bituminous-concrete surface with transversal cracks - Gustieliev, Оleksandr (Academic journal Industrial Machine Building Civil Engineering, 2019)
The method of sealing materials effectiveness evaluation in the repair of bituminous-concrete surface with transversal cracksis offered. Calculation schemes and mathematical models based on the application of the thermo-viscous-elasticity theory forthe prediction of temperature stresses in the sealing material at the contact with the bituminous-concrete surface, taking intoaccount the thermal-technical and thermorheological properties of the materials and the geometric parameters of the bituminous-concreteslabs and the transversal crack. The obtained analytical dependences allow to estimate the service life beforethe loss of sealant compound integrity or adhesive strength of their adhesion with bituminous-concrete surface taking intoaccount annual and daily temperature fluctuations according to the main provisions of the kinetic theory of solid bodiesstrength.
Keywords: bituminous-concrete surface; temperature transversal cracks; sealing materials; thermo-stressed state